International Student Migration: Outcomes and Implications - McGill, Jenny (Journal of International Students, 2013)
The present study examined the possible correlation between six life circumstances of international students (N=124) admitted entry into the United States for the purpose of academic study and their geographic choice of location upon graduation. This paper improves upon the current literature by offering actual migration outcomes (rather than intentions), by including three factors not previously analyzed, and by considering graduate students from a new subject field. The independent variables included: duration of study, scholarship award, doctoral study, participation in optional practical training, application for a temporary work visa, and the economic classification of the student’s country of origin. The dependent variable was student geographic location as of 15 May 2011, categorized as in the United States or outside of the U.S. Data from foreign student graduates (academic years 2000-2011) from 43 countries were analyzed in binary logistic regression.